Study of work attitudes in terms of the performance of health workers in Pampang Community Health Center, Makassar City - Wisudawan B, Owildan; Ahmad, Haslinah; Hasibuan, Ahmad Safii (Sean Institute, 2022)
Optimal performance can be obtained if the employee is enthusiastic and enthusiastic in carrying out his work, and can achieve predetermined targets, quality work quality and in accordance with work standards. Improving the performance of employees is also inseparable from several factors related to the existing systems within the organization. The organizational system must be able to create a climate that can lead to the desire for achievement of all employees. This research was conducted inPampang Health Center Makassar City in 2021. The type of research used is observational with a descriptive approach, namely to find out the description of the performance of health workers inPampang Health Center Makassar City in 2021. The sample of this research was health workers with exhaustive sampling of 26 health workers. The results showed that there were health workers who had good motivation who stated good performance as much as 35.3%, Health workers who stated good self-control stated good performance as much as 57.1%, Health workers who stated good teamwork stated good performance good as much as 42.9%. The conclusion is that health workers play an important role in health services so that they are expected to be able to motivate themselves to improve performance in every process of health services.